Physical Properties of Cervical Mucus of Repeat Breeder Aceh Cattle - Siregar, Tongku Nizwan; Agustina, Iin; Masyitah, Dian; Azhar, Al; Dasrul, Dasrul; Thasmi, Cut Nila; Sulaiman, Rusli; Daud, Razali (Jurnal Veteriner; Vol 18 No 3 (2017)DO - 10.19087/jveteriner.2017.18.3.378, 2017)
This study aimed to investigate the changes in physical properties of cervical mucus of repeat breeder aceh cattle. Subjects were three normal (K1) and repeat breeder (RB) adult female aceh. K1 were post partus cattle >2 months had successful pregrncy by one insemination and had regular cycle twice whereas K2 consisted of repeat breeders, i.e. cattle had normal estrus but failed to be pregnant after three times artificial inseminations. Cervical mucus samples, 50 ml, were collected by aspiration using a sterile catheter and disposable syringe. Catheter was inserted via vagina followed by rectal palpation to direct catheter reached the cornua uterus or vaginal folds. Result of evaluation on the physical properties of cervical mucus from fertile and repeat breeder cattle showed that their cervical mucus was unavailable/small in quantity (0.00 vs. 66.67%), cloudy color (0.00 vs. 66.67%), thick consistency (0.00 vs. 100%), fern pattern (0.00 vs 66.67%), spinnbarkeit (5.16±1.60 vs. 2.83±2.02 cm) and pH values (7.33±0.57 vs 9.33±1.52). It can be concluded that cervical mucus of repeat breeder aceh cattle were lesser in quantity and had cloudier color, thicker consistency, and lower pH than that of fertile aceh cattle.
Keywords: cervical mucus, aceh cattle, repeat breeder